Optimizing mompreneurs’ role in promoting family economic independence through bakery businesses - Basyiruddin Nur; Yeni Elfiza Abbas; Indra Pradana Singawinata; Gustofan Mahmud; Nur Asmila; Rina Pratiwi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This community service program was implemented to encourage homemakers in the Mandosi Permai Housing Complex, Bekasi, to open sustainable home-based bakery businesses. Using participatory design, 22 participants attended a one-day seminar, workshop, and evaluation meeting. The seminar focused on developing a business model that aligns with women's dual roles of domestic and entrepreneurial activities (mompreneurs), while the workshop provided interactive sessions on bread-making practices and cost monitoring. Results indicated that participants improved their ability to identify business model components, gained interest and practical skills in bread-making, and built confidence in managing a micro-enterprise. The program's participatory design helped convey ownership of the entrepreneurial presentation and maintain a core value proposition consistent with consumer demands for freshness, taste, and value. The program and its research agenda illustrate how academic-community partnerships can connect theory and practice in ways that advance women's economic empowerment and family well-being. Implications and future directions for the expansion and sustainability of such programs are discussed.